Los impactos de la globalización en el mundo laboral centroamericano - Pérez Sáinz, Juan Pablo (European Review of Latin American and Caribbean Studies, 2003)
The impact of globalization in the world of labour in Central America This article deals with changes induced by globalization into the world of labour in Central America. The first change affects the proletarization process with the crisis of formal employment, mainly public employment, and the rise of new wage relations in the emerging accumulation model. The main new labour exclusion tendency is represented by transnational migration, the major articulation of the region into globalization. Finally, self-employment, in rural and urban areas, shows the persistence of a broad economy of poverty but also the emergence of new local dynamics that are leading to the fragmentation of national labour markets. In the conclusion a number of issues, analytically relevant beyond Central America, are considered. First, there is a new labour heterogeneity that challenges the analytical distinction between formal and informal employment. Second, territoriality is being redefined and national labor markets are losing their centrality due to transnational migration and local fragmentation. Third, contrary to the past, exclusion tendencies predominate over inclusive ones. And finally, employability is arising as the new way of labour integration. Resumen:Este artículo aborda los cambios inducidos por la globalización en el mundo laboral centroamericano. El primero tiene que ver con el proceso de proletarización que muestra la crisis del empleo formal, especialmente del empleo público, pero también la configuración de nuevas relaciones salariales en las actividades del modelo emergente de acumulación. Una segunda transformación remite a las tendencias de exclusión, donde destaca la migración transnacional, la principal modalidad de inserción de la región en la globalización. Y en tercer lugar se analiza el ámbito del autoempleo, tanto urbano como rural, donde se constata la persistencia de una amplia economía de la pobreza pero también se detectan nuevas dinámicas locales que fragmentan territorialmente a los mercados de trabajo. Se concluye con una serie de reflexiones, que van más allá de Centroamérica, identificando una serie de desafíos analíticos para entender el mundo del trabajo en la globalización. Primero, hay una nueva heterogeneidad ocupacional que cuestiona la pertinencia analítica de los conceptos formal e informal. Segundo, se redefine la territorialidad y los mercados nacionales de trabajo pierden su primacía debido a las migraciones laborales transnacionales y a las dinámicas locales que los fragmentan. Tercero, al contrario del pasado, las dinámicas de exclusión laboral predominan sobre las de integración. Y cuarto, la nueva dinámica de integración laboral se manifiesta en el fenómeno de la empleabilidad.